How students deal with inconsistencies in health knowledge. - Bientzle, Martina; Cress, Ulrike; Kimmerle, Joachim (Medical Education, 2013)
Objectives In their work, health care professionals have to deal daily with inconsistent health information and are confronted with differing therapeutic health concepts. Medical education should prepare students to handle these challenges adequately. The aim of this study was to contribute to a better understanding of how students deal with inconsistencies in health knowledge when they are presented with either a therapeutic concept they accept or one they reject. Methods Seventy-six students of physiotherapy participated in this 2 × 2 experiment with health information (consistent versus inconsistent information) and therapeutic concept (congruent versus contradictory therapeutic concept) as between-group factors. The participants' task was to improve the quality of a text about the effectiveness of stretching; participants were randomly assigned to one of four texts. Knowledge acquisition and text modification were measured as dependent variables. Results Students acquired more knowledge when they worked with a text containing inconsistent information. Medical information that was presented in agreement with a student's therapeutic concept was also more readily acquired than the same information presented posing a contradictory therapeutic concept. Participants modified the contradictory text in order to adapt it to their own point of view. Disagreement resulted in a disregard or devaluation of the information itself, which in turn was detrimental to learning. Conclusions It is a problem when prospective health care professionals turn a blind eye to discrepancies that do not fit their view of the world. It may be useful for educational purposes to include a knowledge conflict caused by a combination of conviction and inconsistent information to facilitate learning processes.